MODIFICACIÓN DE LA PENA EN EL DELITO DE VIOLACIÓN A LA INTIMIDAD POR MEDIOS INFORMÁTICOS; PARA GARANTIZAR EL DERECHO A LA REPARACIÓN INTEGRAL DE LA VÍCTIMA - Elizalde Vivanco, Tatiana Priscila (2019)
The present thesis entitled: "MODIFICATION OF THE PENALTY IN THE CRIME OF VIOLATION OF PRIVACY BY COMPUTER MEANS; TO GUARANTEE THE RIGHT TO THE INTEGRAL REPARATION OF THE VICTIM, "refers to the violation of the right to privacy of people by computer means, it is thus, several objectives are established in order to reform the legal rule so that the person who be violated of their right to privacy have protection and have access to a legal entity, such as the prosecution, where as a victim they guarantee the protection of their personal integrity and due comprehensive reparation since since the act has been committed, the victim suffers damage to morals, thus demonstrating the need to develop a draft reform of the Organic Comprehensive Criminal Code in Article 178, thus increasing the penalty for this illegal act and demanding due comprehensive immediate reparation, which prevents its execution according to the present hypothesis of the investigative work presented below. Likewise, materials and methods were applied to develop the present investigation, through interviews and surveys, in which it was achieved as a result that the legal professionals agree that if there is a violation of privacy by computer means and that they agree with the proposal of the reform to modify the penalty and guarantee the integral reparation to the victim. with the sole purpose of guaranteeing the rights and integral reparation of the person who is violated towards their privacy through computer means.